Последний ученик да Винчи: роман / Н. Н. Александрова - Александрова Наталья Николаевна (Артефакт Детектив, 2011)
Экземпляры: (20170505) / Инвентарный номер: 36082 / Цена: 72.00 / Сис.шифр: Р2 / Авт.знак: А 46 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6